Ultrasound -guided erector spinae plane block (ESPB) versus intravenous opioids based analgesia in patients with rib fractures - Soha Elmansy; Mohammed Abdelkhalek; Sherif Farouk; Randa Shoukry; Ahmed Khames (Egyptian Journal of Anaesthesia, 2023)
ABSTRACTBackground There has been a great interest in the erector spinae plane block (ESPB) to control pain in patients who are presented with rib fractures. ESPB has been shown to achieve adequate analgesia with little adverse effects, although its effectiveness in comparison to other analgesic alternatives has not been sufficiently studied.Aim of the study Our target was to compare the effectiveness of ESPB and opioid based analgesia in relieving pain in rib fractures patients.Methodology Fifty-two patients between 21 and 60 years old, divided into 2 equal groups, received either Ultrasound-guided (US) ESPB with 20 ml of bupivacaine 0.25% or intravenous (IV) morphine 0.1 mg/kg then IV Patient-controlled analgesia (PCA) containing morphine. Assessment of visual analogue scale (VAS) score before and after spirometer exercise at baseline, then at 30 minutes, 6 hours, and 12 hours after the intervention was done. Also Peak Inspiratory Flow Rate (PIFR) was measured by an incentive spirometer, first 12-hour morphine consumption as rescue analgesia was calculated, the incidence of complications was noted, and patients satisfaction was assessed.Results The VAS score was higher in morphine group compared to ESPB group before and after spirometry. PIFR was higher in ESPB group. Less opioid consumption and side effects, along with better patient satisfaction, were recorded in the ESPB group.Conclusion Erector spinae plane block provided superior analgesia and improved respiratory function for IV PCA morphine. Furthermore, ESPB was linked to fewer side effects, less opioid use, and better patient satisfaction.